Spatio-temporal evolution of apparent resistivity during coal-seam hydraulic flushing. (26th February 2018) - Li, Dexing; Wang, Enyuan; Song, Dazhao; Qiu, Liming; Kong, Xiangguo
Abstract: Hydraulic flushing in gas predrainage is widely used, but the hydraulic-flushing effect is evaluated in a traditional way, by determining the desorption volume, moisture content, gas drainage rate and other conventional indices. To verify the rationality and feasibility of the multielectrode resistivity method in the evaluation of coal-seam hydraulic flushing and to research the spatio-temporal evolution of apparent resistivity during hydraulic flushing, a field test was conducted in 17# coal seam at Nuodong Mine, Guizhou. During hydraulic flushing, four stages were defined according to the variation in coal rock resistivity with time, namely, the preparation stage, the sharply decreasing stage, the rapidly increasing stage and the steady stage. The apparent resistivity of the coal rock mass is affected mainly by its own degree of fragmentation and flushing volume. A more serious rupture and a greater flushing volume yield a smaller apparent resistivity during the sharply decreasing stage and a higher resistivity during the stable stage. After three months of gas predrainage, the residual gas content and the gas pressure at different points in the expected affected area decrease below the critical value. Changes in the residual gas content and gas pressure at these points are consistent with the apparent resistivity, which validates the rationality and feasibility of the multielectrode resistivity method in evaluating coal-seam hydraulic flushing.